Aflatoxin levels and hepatitis B infection among corn-eating community in Cebu - Manglicmot, Ailyn G. (1999)
The presence of two risk factors of hepatocellular carcinoma, namely blood AFB1 levels and HBV infection, were determined among a corn-eating community in Cebu. Blood AFB1, a measure of aflatoxin exposure, was determined using an ELISA technique developed and validated in Biotech, UPLB. The prevalence of hepatitis B infection, indicated by HBsAG, was tested using the Monolisa 2nd Generation kit. Alanine aminotransferase was likewise determined to assess the liver function of the study partifipants. The results of this study showed that none of the 103 blood samples tested was found to have AFB1 above 5 ng/ml, the detection limit of the assay used. It was assumed to be in the range of 0-5 ng/ml, probably in picogram levels. The prevalence of hepatitis B virus was found to be 7.7. Among the study population, there were 8 individuals with slight elevations of ALT levels and only one of them is HBsAg positive.Ten corn samples were also tested for AFB1 using the same ELISA method used to test the serum samples and the result showed a mean value of 261.9 ppb. Based on the 157g of corn/capita/day consumption, the study population was exposed to approximately 40.97 ug AFB1/capita/day.Since none of the samples tested was found to have AFB1 levels above the detection limit of the assay used, which is 5 ng/ml, it is possible that the blood AFB1 levels were below 5 ng/ml. Therefore, the assumed levels of the subjects are apparently lower compared with the levels observed in other countries facing the same problem of aflatoxin contamination of staple food. This, however, is not enough evidence that this will not pose any health hazard. To date, no acceptable limit for AFB1 known to be a safe levels has been set. Although, there was no quantified blood AFB1 level detected, it is clear that AFB1 was present in the corn samples analyzed. This study therefore had demonstrated the ingestion of considerable amounts of aflatoxin. Based on previous studies, there was an observed relationship between consumption of aflatoxin-contaminated food and HCC. Thus, it is alarming public health issue and further studies should be conducted to better assess the magnitude of the problem.
Thesis (Master of Science in Public Health)--University of the Philippines Manila.
Keywords: Aflatoxins; Hepatitis B